2021
DOI: 10.1016/j.invent.2021.100380
|View full text |Cite
|
Sign up to set email alerts
|

Step-by-step: Feasibility randomised controlled trial of a mobile-based intervention for depression among populations affected by adversity in Lebanon

Abstract: Background E-mental health interventions may help to bridge the mental health treatment gap. Evidence on their effectiveness is compelling in high-income countries. Not enough evidence has been generated on their use with communities affected by adversity in low- and middle-income countries. The World Health Organization (WHO), the National Mental Health Programme (NMMP) at Ministry of Public Health (MoPH) in Lebanon and other partners have adapted a WHO intervention called Step-by-Step for use wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 37 publications
2
28
1
Order By: Relevance
“…The full program completion rate (completed all sessions) in this study was 37.5% (n = 9) among intervention starters, which was similar to Harper Shehadeh et al (41) and Heim et al (20), 43.2 and 32.8%, respectively. Completion rates (proportion of eligible participants who completed at least three therapeutic sessions in this study were comparable to other SbS studies, with 54.2% in the current study and 62.2% in (41) and 35.9 % in Heim et al (20). The preliminary results showed that full completers showed the greatest improvement, and minimal difference in improvement between full completers (completed all sessions) and partial completers (completed 3-4 sessions) was observed (see Table 4), suggesting the treatment gains between the two groups of completers are comparable.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The full program completion rate (completed all sessions) in this study was 37.5% (n = 9) among intervention starters, which was similar to Harper Shehadeh et al (41) and Heim et al (20), 43.2 and 32.8%, respectively. Completion rates (proportion of eligible participants who completed at least three therapeutic sessions in this study were comparable to other SbS studies, with 54.2% in the current study and 62.2% in (41) and 35.9 % in Heim et al (20). The preliminary results showed that full completers showed the greatest improvement, and minimal difference in improvement between full completers (completed all sessions) and partial completers (completed 3-4 sessions) was observed (see Table 4), suggesting the treatment gains between the two groups of completers are comparable.…”
Section: Discussionsupporting
confidence: 86%
“…Due to the comparable participation rate with previous literature, we suggested that the Chinese SbS was feasible. Compared with Heim et al (20) and Harper Shehadeh et al (41), the non-starting rate (did not start any session) was 36.8% in this current study, which was lower than in other SbS studies (42.6 and 69.2%). Overall dropout rate (completed <4 therapeutic sessions) among those who started the intervention (n = 24) was 45.8% at post-assessment in this study, which was similar to other SbS studies at approximately 50%.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations